Recurrent Myopericarditis and Fulminant Cardiogenic Shock Due to Autoimmune Polyglandular Syndrome 2 - Christopher Lee; Sam Dow; Joanne Lin; Stanislav Henkin; Cynthia Taub (Annals of Internal Medicine: Clinical Cases)
A 34-year-old man presented with acute pericarditis and a small pericardial effusion but rapidly decompensated into cardiac tamponade and fulminant cardiogenic shock, requiring venoarterial extracorporeal membrane oxygenation cannulation. He was diagnosed with autoimmune polyglandular syndrome 2 and was treated with stress dose steroids and an interleukin-1 inhibitor, with improvement in his cardiac function.